THE IMPROVING OF STUDENTS ABILITY IN WRITING RESEARCH BACKGROUND OF CLASSROOM ACTION RESEARCH PROPOSAL BY USING SCIENTIFIC APPROACH - Fenty Napitupulu (LPPM Universitas HKBP Nommensen, 2021)
This study is aimed to know the improvement in writing background of Classroom Action Reseach proposal by using Scientific Approach done by the sixth semester students of English Department of Nommensen University Academic Year 2020/2021.Scientific writing is a way for someone to put the concept of thinking in written form so that other people can understand what is being thought. The method used here is an action research using Scientific Approach.In conducting this classroom action research, the writer divided the action into twocycles. The instrument of collecting data were qualitative data from observation, interview, diary notes, and documentation. Quantitative data were taken from students writing of CAR proposal, which was carried out in the end of everycycle. It is applied for students’ learning in writing Classroom Action research proposal. The students are expected to have logical thinking aspects, data objectivity, vocabulary mastery, use of Enhanced Spelling (EYD), use of effective sentences, and paragraph development. The result showed that Scientific Approach can improve students’ ability to write background of Classroom Action research proposal since inapplying Scientific Approachare found that students are very active in doing observation, questioning, experimenting, associating and communicating so it motivated students to achieve the maximum learning outcomes.